PROJECT FINANCING THROUGH PUBLIC-PRIVATE PARTNERSHIPS IN COLOMBIA: A LOOK INSIDE OF 4G HIGHWAY CONCESSIONS - Duque-Grisales, Eduardo; Vargas-Vargas, Carolina; Patiño-Murillo, Julián; González-Ruiz, Juan David; Becerra, Miguel A. (Journal of Applied Engineering Science, 2021)
This article analyzes the benefits of the financing scheme through Public-Private Partnerships belonging to the Fourth Generation Highway Concessions Program in Colombia. In this program, the Government of Colombia establishes a concession for 25 years on highways and guarantees income through the Collection Difference Compensation Mechanism in years 8, 13 and 18. A case study is presented on the 4G highway "Autopista al Mar 2" in order to identify the commercial risks that may be caused by the difference in collection between the concessionaire and the Colombian government. For this, three traffic scenarios are proposed in order to evaluate their impact on obtaining the Present Value from Toll Revenue - PVTR. The results show that through the project’s finance scheme, this highway is financially viable for the base scenario, and the commercial risk is not stimulated by the collection differences in any of the years 8, 13 or 18; actually, an additional income for the concessionaire of USD $123.19 million is foreseen. Similar results were obtained in the optimistic scenario, with an additional collection of USD $655.90 million, which generates additional revenue to the concessionaire for operation and maintenance costs. However, if there is a 30% decrease in the estimated traffic in the baseline scenario, the PVTR will not be reached within 25 years of the concession and the risk of Collection Difference is activated in the year 18, with an amount of USD $1.11 million; this sum must be provided by the Colombian State to the concessionaire. Finally, these results help to create a roadmap on key issues that require adjustments or improvements in the financing process to drive the effective development of 4G concessions.
Keywords: funding process; highway infrastructure; project finance; public-private partnerships